Evaluation of Left Ventricular Systolic Function and Mass in Primary Hypertensive Patients by Echocardiography. (19th July 2018) - Ali, Shima Ibrahim; Li, Yuman; Adam, Mohamed; Xie, Mingxing
Abstract : Hypertension is an independent risk factor for cardiovascular diseases. The accurate evaluation of cardiovascular risk is of paramount importance in the management of hypertensive patients. Conventional echocardiographic methods have provided the assessment of left ventricular systolic function and mass for many years. Tissue Doppler imaging, 3‐dimensional echocardiography, and speckle tracking echocardiography are newer echocardiographic modalities for the left ventricular systolic function and mass quantification. The major emphasis of this review is to evaluate the left ventricular systolic function and mass by conventional and newly developed echocardiographic in hypertensive patients.